The Chemical Constituents and Biological Activities from Mitrephora tomentosa and Lumnitzera littorea - Puttandon Wongsomboon (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
The phytochemical investigation of the methanol extracts of the leaves and twigs of Mitrephora tomentosa led to the isolation and characterization of 12 compounds including six new class of polyacetylenic ester, dihydrobenzofuran lignan natural products (A1-A6), along with two known polyacetylenic acids (A7 and A9), one known dihydrobenzofuran lignan (A8) and three known furofuran lignans (A10-A12). The structures of these compounds were confirmed by NMR and mass spectrometric analyses. Compounds A3, A5 and A6 exhibited moderate antimalarial activities against the P. falciparum TM4/8.2 and K1CB1 strains. A new macrocyclic lactone, 12-hydroxycorniculatolide A (B1), along with two known compounds, corniculatolide A (B2) and 12-hydroxy-11-O-methylcorniculatolide A (B3) were isolated from the methanolic extract of the twigs from Lumnitzera littorea. All compounds were characterized by spectroscopic data